THE URGENCY OF TEACHERS INSTILLING ISLAMIC VALUES IN STUDENTS - Zailani, Zailani (Proceeding International Seminar of Islamic Studies, 2024)
The cultivation of Islamic values in students is crucial to education. Teachers play a very significant role in instilling Islamic values in students, especially at an early age. Research indicates that instilling Islamic values in young children requires appropriate planning, implementation, and evaluation by teachers. This is because, at this age, students should have developed a sense of responsibility, compassion, and independence in accordance with their moral developmental stage. Additionally, a teaching approach that helps teachers connect learning materials to students' real-life experiences can also aid in instilling Islamic values. Character development programmes and family-based tolerance values integrated into learning are helpful in this regard. Research findings also suggest that teachers believe honesty in children should be built on the foundation of monotheism (tauhid). Therefore, instilling Islamic values in students is crucial and requires special attention, especially during childhood.